KEBERADAAN TOKO SWALAYAN ALFAMART DAN INDOMARET TERHADAP USAHA KECIL YANG ADA DI PONTIANAK BARAT - NIM. A1012191215, JERICO MARULI TUA SITORUS (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT The existence of Alfamart and Indomaret supermarkets on the one hand shows good macro economic development and also has a positive impact on absorbing local labor and increasing investment. However, on the other hand, this economic development has apparently triggered unrest among small and medium businesses because of the fairly rapid presence of Alfamart and Indomaret supermarkets, and it is possible that over time it will have an increasingly negative impact on small traders or small businesses and middle class in general. This also happens with small businesses (warungs) in the West Pontianak area because many Alfamart and Indomaret supermarkets have mushroomed. Based on data from the Pontianak City Cooperatives, Micro Enterprises and Trade Department, the number of Alfamart and Indomaret supermarkets in the West Pontianak area of Pontianak City is 28 units, of which the number of Alfamart supermarkets is 14 units and the number of Indomaret supermarkets is 14 units. Seeing the presence of quite a lot of Alfamart and Indomaret supermarkets, of course this has an impact on the economic conditions of small businesses in West Pontianak. The negative impacts resulting from the existence of Alfamart and Indomaret supermarkets seen from the perspective of small businesses include: decreased consumers, decreased sales turnover, and less competitive prices. This clearly raises legal implications from the aspect of unfair business competition. Therefore, the role of the Pontianak City Government is needed in overcoming the occurrence of unhealthy business competition between Alfamart and Indomaret supermarkets for small businesses in West Pontianak. In this research, the author used empirical research methods or also known as analytical descriptive field research with qualitative data analysis methods. Based on the research results, it was concluded that the legal implication of the existence of Alfamart and Indomaret supermarkets for small businesses in West Pontianak in terms of unhealthy business competition law is market control activities. Market control is one of the activities that is prohibited according to the provisions of Article 19 of Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. The form of market control activities carried out by Alfamart and Indomaret supermarkets is with the aim of preventing small business actors from carrying out the same business activities in the relevant market and preventing consumers or stall customers from carrying out business relations with the stalls. So far, the Pontianak City Government has not played a role in overcoming unhealthy business competition between Alfamart and Indomaret supermarkets and small traders (warungs), especially market control in the West Pontianak area. In fact, in the provisions of Article 39 letter a of Pontianak City Regional Regulation Number 2 of 2017 concerning the Arrangement and Development of People's Markets, Shopping Centers and Supermarkets, which states that